Coaching with NLP for dummies - Burton, Kate 1962- (John Wiley & Sons, 2011)
How to become an NLP practitioner?or supercharge your coaching skills with NLP One of the most popular methods for helping people achieve their life aspirations?Neuro-Linguistic Programming, or NLP, holds the key to remaking one's future. NLP encourages users to re-create the thought patterns common to those who excel, a process that helps gradually weed out negative or habitual thinking. Using the key elements of NLP?developing a coaching relationship, shedding light on patterns, managing emotional states, and shaping an agenda for change?this practical, inspiring guide offers the t.
Keywords: Employees -- Coaching of; Neurolinguistic programming; Programmation neurolinguistique; Employees; Coaching of